Caracterización bromatológica y microbiologica de la harina con base en cáscaras de cacao (Theobroma cacao L.), para la elaboraciónd e galletas. - Romero Rojas, Rosa Angélica (2017)
The objective of the present investigation was to characterize the flour based of cocoa shell (Theobroma cacao L.) at the bromatological and microbiological level for the production of cookies of oats. A completely randomized design was applied, with four treatments and five replicates. For the determination of differences between treatments, Tukey's multiple range test was used at 5% probability, treatments corresponded to four interclonal cocoa lines (DIRCYT – H. 258, DIRCYT – H. 259, DIRCYT – H. 263 and DIRCYT – H. 265) from the Experimental Farm "La Represa". Bromatological variables were analyzed (moisture, dry matter, ash, organic matter, ethereal extract, total nitrogen, crude fiber, ELNN and energy), microbiological variables (aerobic mesophiles, total coliforms and molds - yeasts), sensory variables (color, smell, taste, texture and general acceptability) and economic variables (net profit, B / C ratio and profitability). Based on the statistical analysis, it was determined that there was no statistical significance among the treatments in the obtainment of flour, because yes a difference mathematics for the variables organic matter, total nitrogen, crude fiber and energy. However, T1 was noted for presenting average values according to NTE INEN 0616: 2006 in terms of humidity (6.73%) and total nitrogen (8.14%). In the microbiological analysis it was observed that the evaluated treatments complied with the stipulated in NTE INEN 0616: 2006, being suitable for human consumption. The non - parametric Kruskal - Wallis test and Analysis of Principal Components were used for the sensory evaluation of the biscuits of oats. The treatment with the highest acceptability was T4, indicating that the substitution of the flour of wheat for the flour of cocoa shell in a 25% does not influence the organoleptic properties of the baked product. With respect to the economic analysis it is indicated that the B/C ratio for the production of flour is $ 1.20 with a yield of 0.500 kg and in the production of cookies is $ 1.12 with a yield of 200 units with a weight of 4 g on a dry basis; for each dollar invested a return was obtained of $ 0.20 and 0.12 with a profit of 20.18 and 11, 86% respectively.